Influência de características físicas e química dos materiais de abutments de implantes em zircônia e titânio na adesão e viabilidade de células epiteliais gengivaiS OBA-9 - Rigolin, Maria Silvia Mauricio [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Given the need for effective early mucosal barrier around dental implants, the present study evaluated, in vitro, the influence of physical and chemical characteristics of materials simulating abutments implants surfaces in titanium (T) and zirconium (ZrO2) on gingival epithelial cells OBA-9 adhesion. For this study, disks-shaped samples (n=13) of titanium and zirconium were tested, and as positive and negative control groups, bovine enamel disks (BE), and glass coverslips (GCS), respectively. Previously the cellular adhesion surface roughness (Ra), surface free energy (SFE) and the chemical composition of specimens by X-ray Spectrometer Dispersive Energy in Scanning Electron Microscope (SEM) were evaluated. After the periods of cellular adhesion, 1 and 24 hours, the cellular viability was evaluated by MTT Assay (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) and the morphology of the epithelial cells adhered to the surfaces was analyzed using the SEM. The data of cell viability were statistically evaluated by two-way ANOVA (Material and period of analysis), while the SFE data were submitted to Kruskal-Wallis and Mann-Whitney tests, considering a significance level of 5%. The T specimens showed the highest values of SFE (6.2 N/m), followed by ZrO2 (5.8 N/m), GCS (4.9 N/m), and BE (4.7 N/m). It was observed that the factors material (p = 0.336) and periods of analysis (p = 0.400) showed no effect on cell viability data, as well as the interaction between them (material* period of analysis, p = 0.559). The analysis of cell morphology showed that cells adhered to the T and ZrO2 surfaces presented similar spreading, which was higher compared to the BE and GCS surfaces. It was concluded that there was no difference between the cellular adhesion to different materials for implant abutments, T and ZrO2, in evaluated periods. However, cell spreading was qualitatively higher in rougher surfaces and greater titanium and zirconia...

Dada à necessidade de uma efetiva barreira tecidual precoce ao redor dos implantes osseointegrados, o presente estudo avaliou, in vitro, a influência das características físicas e químicas de materiais simulando superfícies de abutments de implantes em titânio (T) e zircônia (ZrO2) na adesão de células epiteliais gengivais OBA-9. Para este estudo foram utilizados espécimes em forma de discos (n=13) de titânio e zircônia, e como controles positivo e negativo, discos de esmalte bovino (EB) e lamínulas de vidro (LV), respectivamente. Foram avaliadas previamente a adesão celular a rugosidade superficial (Ra), energia livre de superfície (ELS) e os elementos químicos presentes na superfície identificados por meio de Espectrômetro de raios-X por Dispersão de Energia em Microscópio Eletrônico de Varredura (MEV). Após a adesão celular em 1 e 24 horas, foram avaliadas a viabilidade celular por meio do MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide); e a morfologia das células aderidas sobre as superfícies por meio de MEV. Os dados de viabilidade celular foram avaliados estatisticamente pelo teste de ANOVA a dois critérios fixos (“material” e “período de análise”), enquanto os dados de ELS foram submetidos aos testes de Kruskal-Wallis e Mann-Whitney, considerando um nível de significância de 5%. A superfície de T obteve o maior valor de ELS com 6,2N/m, seguida pela ZrO2 com 5,8N/m, LV com 4,9N/m, e com o menor valor o EB com 4,7N/m. Foi observado que os fatores material (p=0,336) e período de análise (p=0,400) não apresentaram efeito sobre os dados de viabilidade celular, assim como a interação entre eles (material*período de análise, p=0,559). A análise da morfologia celular mostrou que as células aderidas às superfícies de T e ZrO2 apresentaram espraiamento semelhante, sendo este maior quando comparado as superfícies de EB e LV. Concluiu-se que não houve diferença entre a adesão...
Keywords: Celulas - Adesão; Celulas; Titanio; Zirconio; Titanium